2020
DOI: 10.5937/ekopolj2001223m
|View full text |Cite
|
Sign up to set email alerts
|

Research on tourists' attitudes on the potential of Goč mountain for the development of eco-tourism

Abstract: The aim of the research is to examine the views of tourists on the possibilities for the development of ecotourism on the mountain Goč, with a view to the more intensive tourist development of this mountain. Special attention is paid to the analysis of possibilities for expanding the existing tourist offer, additional attractive contents and activities, which would contribute to the greater competitiveness of this mountain in the ecotourism market. The survey method was used to collect primary data in the rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Numerous authors have analysed relationships between visitors' sociodemographic characteristics (such as gender, age, place of residence, educational level, employment status and income) and motivation (Kim et al 2008;Chen et al 2014;Newton et al 2018;Milohnić et al 2019;Moniz et al 2020;Silva et al 2020;Milićević et al 2020). Motives such as relaxation, escape, nature or recreation have frequently emerged in different studies, although the most influential factor may vary according to the visitors' sociodemographic characteristics (Magadan-Díaz & Rivas-García 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous authors have analysed relationships between visitors' sociodemographic characteristics (such as gender, age, place of residence, educational level, employment status and income) and motivation (Kim et al 2008;Chen et al 2014;Newton et al 2018;Milohnić et al 2019;Moniz et al 2020;Silva et al 2020;Milićević et al 2020). Motives such as relaxation, escape, nature or recreation have frequently emerged in different studies, although the most influential factor may vary according to the visitors' sociodemographic characteristics (Magadan-Díaz & Rivas-García 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…One of the most beautiful possibilities for children and adults is a full-day walk through the dense forests while collecting medicinal herbs, picking mushrooms, wild strawberries and blueberries, and encountering wild horses that run free on green pastures (Ivanovski & Popović 2018;Josimovic & Crncevic 2012). The existing natural resources should be a significant factor in the current intensive tourism development of mountains generally, and particular emphasis should be placed on the development of ecotourism (Milićević et al 2020).…”
Section: Study Areamentioning
confidence: 99%
“…One of the most frequently researched topics in hospitality probably is identifying the attributes that actually contribute to hotel selection, booking, experience quality, guests" satisfaction and loyalty. Whereas, in academic literature, researches have shown that what hotel guests often want usually depends on their own individual specific needs, guests' needs vary from hotel to hotel, from destination to destination (Milićević et al, 2020). Such is the case with Israeli hotels for disabled guests, where Poria et al's (2011) research found that while staying at the hotel, guests faced difficulties with physical surroundings and customer service and interactions.…”
Section: Guest Experience and The Importance Of Hotel Attributesmentioning
confidence: 99%